Halogen-free flame-retardant polyolefin material and application thereof in preparation of nuclear power cable material

By using halogen-free flame-retardant polyolefin materials in nuclear power cable materials, combined with the side-based polyethylene, antioxidant and graphene multifunctional flame-retardant synergist of flame retardant units, the lack of radiation durability and thermal aging performance of the material is solved. Problem, higher flame retardant performance and longer service life are achieved.

CN119144091AActive Publication Date: 2024-12-17UNIV OF SCI & TECH OF CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411295117.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-15
Publication Date
2024-12-17
Estimated Expiration
2044-09-15

AI Technical Summary

Technical Problem

Existing polymer materials have problems in nuclear power cables with insufficient radiation durability and thermal aging performance, poor dispersion of flame retardant and antioxidant migration problems, which affect the long-term service life of the material.

Method used

Using halogen-free flame-retardant polyolefin materials, the polyethylene, multifunctional crosslinking agent and antioxidant are grafted in the polyolefin, combined with microencapsulated halogen-free flame-retardant and graphene multifunctional flame-retardant Synergist, improves the flame retardant properties, radiation resistance and thermal aging life of the material.

Benefits of technology

The flame retardant performance, radiation resistance and thermal aging life of polyolefin materials are significantly improved, the amount of flame retardant is added is reduced, the service life of the material is extended, and the overall performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144091A_ABST
    Figure CN119144091A_ABST
Patent Text Reader

Abstract

The invention discloses a halogen-free flame-retardant polyolefin material and application thereof in preparation of a nuclear power cable material. According to the halogen-free flame-retardant polyolefin material, polyethylene-vinyl acetate is hydrolyzed and grafted with different flame-retardant structural units, so that not only can the physical properties of polyolefin be improved, but also the flame-retardant property and the flame-retardant level of the polyolefin can be improved; in addition, the halogen-free flame-retardant polyolefin material provided by the invention has excellent thermal aging life and radiation resistance, and the comprehensive physical properties such as flame retardance, radiation resistance, thermal aging life and the like of the polyolefin cable material for the nuclear power station can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a halogen-free flame-retardant polyolefin material and application thereof in the preparation of nuclear power cable materials. Background Art

[0002] At present, the world's most advanced high-temperature gas-cooled reactor, CAP1400 nuclear power high-safety cables and their core key materials, including power, control, instrumentation, high temperature, network communication, coaxial and other series of cables and insulation, sheath, filling and other key materials. Due to the abundance of raw materials, low prices, easy processing and molding, good electrical insulation properties and excellent comprehensive performance, polyolefins are widely used in nuclear power plant cable materials. The high safety performance of nuclear power cables is reflected in the long service life at 90°C (≥60 years), resistance to high radiation doses (≥2500kGy), functional integrity under design accident conditions, and at the same time, it must meet mechanical properties, electrical properties, flame retardant properties, acid and alkali medium resistance and other properties.

[0003] The new generation of nuclear power requires that the cable still has a good elongation after being irradiated with 2500kGy high-energy rays, but the radiation resistance of general polymer materials is poor. In order to improve the radiation stability of polymers, radiation protection agents can be added to polymers to extend the service life of the material in strong radiation fields. The first type is sacrificial anti-radiation agents. This type of protective agent is mainly some free radical scavengers, which receive radiation energy from irradiated substances, protect the irradiated substances and decompose themselves. The second type is sponge-type anti-radiation agents. This type of protective agent includes naphthalene, anthracene, phenanthrene, o-phenol and other types rich in benzene ring structures. It can transfer the radiation energy absorbed by the main components of the irradiated polymer to itself, and then release it in the form of light or heat, and the polymer itself only causes very little damage. However, during the use of nuclear power cables, these two types of anti-radiation agents are easy to migrate to the environment due to their small molecular weight in high-temperature use environments, causing physical losses. Excessive addition will affect the comprehensive physical properties of the cable materials.

[0004] The service life of nuclear power cables at 90°C is required to be greater than 60 years. Antioxidants are widely used in nuclear power cables to improve their thermal aging life. However, antioxidants are consumed during service, either due to chemical loss caused by antioxidant activity or physical loss caused by their migration to the environment, both of which lead to polymer degradation. Among them, the migration of antioxidants has always been a major problem affecting the life of nuclear power cables. Antioxidant macromolecularization or immobilization is an effective way to solve the above problems, so that the migration of synthetic antioxidants is limited.

[0005] In order to obtain better flame retardant properties, it is necessary to add a higher content of flame retardant to nuclear power cable materials. Today's trend of flame retardants is halogen-free and environmentally friendly, and halogen-free flame retardants are increasingly used in cable materials. The aluminum hydroxide and magnesium hydroxide flame retardants commonly used in cable materials have problems such as poor dispersibility, loose carbon layer, poor carbon layer shell performance, and large usage. Intrinsic flame retardant, also called reactive flame retardant, refers to adding the reaction system during the polymer polymerization process, participating in the reaction in the form of monomers, and becoming part of the polymer through chemical bonding. It has little effect on the physical and mechanical properties of the polymer, and the flame retardant performance is long-lasting. However, there are few reports on intrinsic flame retardant polyolefins.

[0006] Studies have shown that phosphites containing +3-valent phosphorus are a type of commonly used flame retardant antioxidants. Their mechanism of action is to act as a hydroperoxide decomposer. They can reduce the hydroperoxides released by polymer materials to alcohols, while they themselves are oxidized to phosphates. Phosphorus-containing compounds are an excellent type of flame retardant. 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO, phosphorus is +1 valence) and diphenylphosphinoyl chloride (DC, phosphorus is +1 valence) are new flame retardant intermediates. Flame retardants containing low-valent phosphorus mainly improve flame retardancy through gas phase flame retardant mechanisms; in addition, anthracenecarboxylic acid (ACA) contains a benzene ring structure, which has the effect of promoting carbonization and flame retardancy. These substances can not only effectively scavenge free radicals and play an antioxidant role, but also have certain flame retardant and anti-radiation effects. There are no reports on the grafting of low-valent phosphorus-containing flame retardants and polyphenyl ring compounds on the main chain of polyolefins. Therefore, it is of great significance to use DOPO, DC containing low-valent phosphorus elements and benzene ring structures and anthracenecarboxylic acid grafted polyolefins containing multiple benzene ring structures to prepare halogen-free flame-retardant polyolefin materials for nuclear power plants to improve the flame retardancy, radiation resistance and thermal aging life of polyolefin composites. Summary of the invention

[0007] The present invention aims at the problems existing in the prior art and provides a halogen-free flame-retardant polyolefin material and its application in the preparation of nuclear power cable materials. The present invention can not only give the polyolefin cable material good flame-retardant properties, but also solve the problems of long-term thermal aging and radiation durability of nuclear power polyolefin cable materials.

[0008] The halogen-free flame-retardant polyolefin material of the present invention comprises the following raw materials in parts by mass:

[0009] 5-45 parts of polyolefin, 40-95 parts of flame retardant unit side-grafted polyethylene, 0.5-5 parts of multifunctional cross-linking agent, and 0.5-4 parts of antioxidant.

[0010] The polyolefin is selected from one or more of polyethylene, maleic anhydride grafted polyethylene, polypropylene, maleic anhydride grafted polypropylene, ethylene-vinyl acetate copolymer, maleic anhydride grafted polyethylene-vinyl acetate copolymer, polyethylene-octene copolymer, maleic anhydride grafted polyethylene-octene copolymer, ethylene propylene diene rubber, maleic anhydride grafted ethylene propylene diene rubber, styrene-butadiene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer or maleic anhydride grafted hydrogenated styrene-butadiene-styrene block copolymer, and mixed in any proportion.

[0011] The antioxidant is selected from one or more of phenolic antioxidants, phosphorus-containing antioxidants, sulfur-containing antioxidants or copper-resistant agents and mixed in any proportion.

[0012] The phenolic antioxidant is selected from pentaerythritol tetrakis[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, Phenyl ) Propionic acid One or more of n-octadecyl alcohol ester, N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine or triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate] are mixed in any proportion.

[0013] The phosphorus-containing antioxidant is selected from tris[2,4-di-tert-butylphenyl] Phosphites One or more of bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite or tetrakis(2,4-di-tert-butylphenol)-4,4'-biphenyl diphosphite are mixed in any proportion.

[0014] The sulfur-containing antioxidant is selected from one or more of dilauryl thiodipropionate, distearyl thiodipropionate, 4,4'-thio(6-tert-butyl-3-methylphenol), 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 6,6'-di-tert-butyl-2,2'-thiodi-p-cresol or pentaerythritol tetrakis(3-laurylthiopropionate) and mixed in any proportion;

[0015] The anti-copper agent is selected from N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

[0016] The multifunctional crosslinking agent is selected from one of triallyl cyanurate, triallyl isocyanurate, trimethylol propane trimethacrylate, trimethylol triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, or a mixture of several of them in any proportion.

[0017] The flame retardant unit side-grafted polyethylene is composed of ethylene-vinyl acetate copolymer EVA hydrolyzed and grafted with different flame retardant structural units, wherein the flame retardant structural unit is a flame retardant containing phosphorus or a benzene ring structure; and the grafting amount of the flame retardant structural unit is 15-35%.

[0018] The flame retardant structural unit is selected from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), diphenylphosphinyl chloride (DC) or anthracenecarboxylic acid (ACA), etc. The corresponding structural formula is shown below:

[0019]

[0020] The flame retardant unit side group grafted polyethylene is prepared by a method comprising the following steps:

[0021] Step 1: Add EVA to the solvent and stir, and heat to 40°C. After EVA is completely dissolved, add sodium hydroxide ethanol solution and stir at this temperature for 2-5 hours for hydrolysis, then add hydrochloric acid solution for neutralization reaction for 5-10 minutes; after the reaction is completed, pour the reaction solution into distilled water and stir continuously until all the precipitates are precipitated, filter and wash, cut the precipitate into pieces and put it into an 80°C oven for drying for 12 hours to obtain EVA-OH product.

[0022] Step 2: EVA-OH is grafted with a flame retardant containing a flame retardant structural unit, including the following three methods:

[0023] Method 1: Add EVA-OH to the solvent and stir, and heat to 40°C. After EVA-OH is completely dissolved, add diphenylphosphine chloride to the system, stir for 12 hours through nitrogen, wash and dry with anhydrous methanol to obtain flame-retardant unit side group DC grafted polyethylene (EVA-DC).

[0024] Method 2: Add EVA-OH to the solvent and stir, and heat to 40°C. After EVA-OH is completely dissolved, add anthracenecarbonyl chloride ACA-Cl dropwise to the above solution, stir for 12 hours through nitrogen, wash with anhydrous methanol and dry to obtain flame-retardant unit side group ACA grafted polyethylene (EVA-ACA).

[0025] The anthracenecarbonyl chloride is prepared by the following method: using anthracenecarboxylic acid as a raw material, adding thionyl chloride and chloroform into a reaction system, heating to 40-60°C in a nitrogen atmosphere for reaction; cooling to room temperature after the reaction, and recovering the solvent by rotary evaporation to obtain a viscous liquid product, namely anthracenecarbonyl chloride ACA-Cl.

[0026] Method 3: Add EVA-OH and DOPO to the solvent, stir, and heat to 40°C. After EVA-OH and DOPO are completely dissolved, add carbon tetrachloride dropwise to the above solution, stir for 12 hours through nitrogen, wash with anhydrous methanol and dry to obtain flame-retardant unit side group DOPO grafted polyethylene (EVA-DOPO).

[0027] Using the first route, the raw materials are composed of the following by mass:

[0028] 65-85 parts of ethylene-vinyl acetate copolymer EVA, 50-200 parts of ethanol, 0.5-1.5 parts of sodium hydroxide, 50-100 parts of 1 mol / L HCl solution, 200-300 parts of solvent, and 15-35 parts of diphenylphosphine chloride.

[0029] Using the second route, the raw materials are composed of the following by mass:

[0030] 65-85 parts of ethylene-vinyl acetate copolymer EVA, 50-200 parts of ethanol, 0.5-1.5 parts of sodium hydroxide, 50-100 parts of 1 mol / L HCl solution, 200-300 parts of solvent, 15-35 parts of anthracenecarboxylic acid, and 15-35 parts of dichlorothionyl.

[0031] Using the third route, the raw materials are composed of the following by mass:

[0032] Ethylene-vinyl acetate copolymer EVA 65-85 parts, ethanol 50-200 parts, sodium hydroxide 0.5-1.5 parts, 1 mol / L HCl solution 50-100 parts, solvent 200-300 parts, DOPO 15-35 parts, carbon tetrachloride 15-35 parts.

[0033] The solvent is selected from any one or more of ethanol, N,N-dimethylformamide, tetrahydrofuran, dichloromethane, chloroform, and 1,4-dioxane. The mass fraction of the above solvents is the total amount of solvents used in the preparation process.

[0034] The method for preparing the halogen-free flame-retardant polyolefin material of the present invention comprises the following steps:

[0035] Polyolefin and flame retardant unit side-grafted polyethylene are weighed according to the proportion and mixed in an internal mixer at 140-200°C for 5-20 minutes, and then a multifunctional crosslinking agent and an antioxidant are added. After mixing evenly, the pellets are extruded and granulated at 140-200°C to obtain pellets.

[0036] The invention discloses an application of the halogen-free flame-retardant polyolefin material in preparing an insulating layer of a conductive core of a cable for a nuclear power station.

[0037] The granules are used as the coating material of the insulation layer of the cable conductive core, and are subjected to irradiation crosslinking treatment, specifically, the crosslinking treatment is carried out under a 10KW, 10MeV electron beam with an irradiation dose of 100KGy to 2400KGy.

[0038] The halogen-free flame-retardant polyolefin material of the present invention comprises the following raw materials in parts by mass:

[0039] 10-30 parts of polyolefin, 25-40 parts of flame retardant unit side-group grafted polyethylene, 40-50 parts of microencapsulated halogen-free flame retardant, 1-5 parts of multifunctional flame retardant synergist, 1-3 parts of multifunctional cross-linking agent, 0.5-2 parts of lubricant, and 1-4 parts of antioxidant.

[0040] The definitions of polyolefin, flame retardant unit side-grafted polyethylene, multifunctional crosslinking agent and antioxidant are the same as above.

[0041] The microencapsulated halogen-free flame retardant consists of a shell material and a core flame retardant.

[0042] The shell material is selected from one of silica gel, hyperbranched carbon-forming agent, and polyphosphazene; the core flame retardant is selected from one of aluminum hydroxide, magnesium hydroxide, magnesium aluminum double hydroxide, zinc aluminum double hydroxide, magnesium iron double hydroxide, zinc iron double hydroxide, nickel iron double hydroxide, ammonium polyphosphate, pentaerythritol, melamine, melamine phosphate, melamine cyanurate, inorganic aluminum hypophosphite, organic aluminum hypophosphite, triazine carbon-forming agent, piperazine pyrophosphate, zinc borate, zinc aluminate, zinc stannate, and low-melting point glass powder, and one or more thereof are mixed in any proportion.

[0043] The mass ratio of the shell material to the core flame retardant is (10-30):(70-90).

[0044] The microencapsulated flame retardant can be prepared according to the methods disclosed in Chinese Patent No. 201410016870.8 and Chinese Patent No. 200810156885.9, respectively, and the microencapsulated flame retardant having a shell layer of a hyperbranched carbon-forming agent and a silica gel.

[0045] The multifunctional flame retardant synergist is composed of nanoparticle anti-radiation agent and graphene. The nanoparticle anti-radiation agent is selected from one or more of tungsten oxide, bismuth oxide, bismuth carbonate, rare earth metal oxide, and nano silicon dioxide and mixed in any proportion. The rare earth metal in the rare earth metal oxide is one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, and europium.

[0046] Furthermore, the preparation method of the multifunctional flame retardant synergist comprises the following steps:

[0047] The graphene is mixed with water and ultrasonically treated for 20-40 minutes, and then the corresponding precursor of the nanoparticle anti-radiation agent is added. Under nitrogen protection and stirring, an alkaline regulator is added dropwise to make the pH of the system 9-11. After the addition is completed, the temperature is increased for heating reaction. After the reaction is completed, centrifugal separation, water washing, alcohol washing and drying are performed to obtain graphene loaded with nanoparticle anti-radiation agent, which is a multifunctional flame retardant synergist.

[0048] The corresponding precursor of the nanoparticle anti-radiation agent is tungsten chloride, bismuth chloride, chloride-based rare earth metal salt or tetraethyl orthosilicate.

[0049] The mass ratio of the graphene, the corresponding precursor of the nanoparticle anti-radiation agent, and water is 3:(2-5):300.

[0050] The alkaline regulator is a 25wt% ammonia solution or a 1mol / L sodium carbonate solution.

[0051] The heating reaction can be carried out by heating the mixture to 80° C. in a water bath for 24 hours, or by transferring the mixture to a hydrothermal reactor for a hydrothermal reaction at 180° C. for 12 hours.

[0052] The lubricant is selected from one or more of silicone powder, zinc stearate, paraffin wax and PE wax.

[0053] The preparation method of the halogen-free flame-retardant polyolefin material of the present invention comprises the following steps:

[0054] The polyolefin and flame retardant unit side-grafted polyethylene are weighed according to the proportion, mixed in an internal mixer at 140°C-200°C until uniform, and then microencapsulated halogen-free flame retardant, multifunctional flame retardant synergist, multifunctional cross-linking agent, antioxidant and lubricant are added. After mixing evenly, the pellets are extruded and granulated at 140°C-200°C to obtain pellets.

[0055] The invention discloses an application of the halogen-free flame-retardant polyolefin material in preparing an outer sheath layer of a conductive core of a cable for a nuclear power station.

[0056] The obtained granules are used as the outer sheath material of the cable conductive core, and are subjected to irradiation cross-linking treatment, specifically, the cross-linking treatment is carried out under 10KW, 10MeV electron beam with an irradiation dose of 80KGy to 240KGy.

[0057] Compared with the prior art, the excellent effects of the present invention are embodied in:

[0058] (1) The present invention selects flame retardant unit side group grafted polyethylene as an important component of the matrix material, and the high grafting rate is the high benzene ring content of the resin, thereby giving the polyolefin insulation material and the sheath material excellent radiation resistance; the multifunctional flame retardant synergist is a graphene hybrid loaded with nanoparticle anti-radiation agent, and the graphene loaded with nanoparticle anti-radiation agent is obtained by hybridizing the nanoparticle anti-radiation agent with graphene through a hydrothermal method or a co-precipitation method, and mixing the nanoparticle anti-radiation agent with the resin material in a molten state in an internal mixer or an extruder, with the purpose of realizing the delamination or intercalation nano-composite dispersion state of the graphene in the multifunctional flame retardant synergist in the sheath material, which is beneficial to the effect of the graphene and the nanoparticle anti-radiation agent in blocking radiation rays; the present invention disperses the hybrid graphene multifunctional auxiliary agent with high radiation resistance in the form of a nano-composite in the flame retardant unit side group grafted polyethylene with high phenyl content and the polyolefin material with excellent radiation resistance, thereby improving the radiation resistance of the sheath material of the nuclear power plant.

[0059] (2) The graphene in the functional flame retardant synergist of the present invention is dispersed in the polymer matrix in a delaminated or intercalated state, which can exert a lamellar barrier and a maze effect; when the sheath material is immersed in different chemical medium materials, the path of the chemical medium penetrating into the sheath material becomes longer and the migration rate becomes slower, thereby improving the medium resistance of the sheath material.

[0060] (3) The flame-retardant unit side-grafted polyethylene selected in the present invention is an important component of the base material, which gives the polyolefin insulation material an oxygen index as high as 24%, reaching the V-2 level of vertical combustion. The flame-retardant unit side-grafted polyethylene can significantly improve the flame retardant properties, mechanical properties and insulation resistance of the polyolefin insulation material.

[0061] In addition, microencapsulated halogen-free flame retardant is selected as the main flame retardant. Due to the protective effect of the polymer shell, the dispersibility and compatibility of the core flame retardant can be improved, thereby improving the comprehensive performance of the sheath material; the shell material and the core flame retardant can play a synergistic flame retardant role during combustion, further improving the flame retardant effect of the flame retardant; the flame retardant unit side group grafted polyethylene is also selected in the polyolefin sheath material of the present invention to play a synergistic flame retardant role with the microencapsulated flame retardant. The flame retardant unit side group grafted polyethylene can play a gas phase flame retardant role of low-valent phosphorus, and the added halogen-free flame retardant The agent plays a condensed phase flame retardant role, and the two flame retardant mechanisms work together to reduce the flame spread rate and heat release, thereby improving the flame retardant performance; the graphene multifunctional additive dispersed in the sheath material in a nano state can further play a multi-component synergistic flame retardant role with the microencapsulated flame retardant, further improving the flame retardant properties of the polyolefin sheath material; the flame retardant unit side-group grafted polyethylene, microencapsulated halogen-free flame retardant, and multifunctional flame retardant synergist work together to reduce the amount of flame retardant added when reaching the same flame retardant level, thereby improving the comprehensive physical properties of the polyolefin sheath material.

[0062] (4) The present invention disperses the graphene loaded with nanoparticle anti-radiation agent in the sheath material in a delaminated or intercalated state, which is beneficial to exerting the maze effect and sheet barrier effect of the nanosheet layer during high-temperature thermal aging, slowing down the migration rate of the antioxidant and extending the migration path, thereby slowing down the loss rate of the antioxidant and maintaining an excellent thermal aging effect for a long time; the low-valent (+1 valence) phosphorus element in the flame-retardant unit side-grafted polyethylene can play an auxiliary antioxidant role as a hydroperoxide decomposer, which can reduce the hydroperoxide released by the polymer material to alcohol, while being oxidized to phosphate ester itself; the benzene ring structure in the flame-retardant unit side-grafted polyethylene can not only effectively remove the free radicals generated by aging in the polyolefin material, play an antioxidant role, but also improve the temperature resistance grade, long-term aging resistance and thermal aging life of the polyolefin composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 Phosphorus spectra (a) and hydrogen spectra (b) of DOPO and EVA-DOPO.

[0064] Figure 2 HRR and THR curves of EVA and EVA-DOPO.

[0065] Figure 3 The hydrogen spectra of EVA-OH (a) and EVA-ACA (b).

[0066] Figure 4 The hydrogen spectrum (a) and phosphorus spectrum (b) of EVA-DC. DETAILED DESCRIPTION

[0067] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. Based on the examples in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0068] Embodiment 1:

[0069] a. Preparation of EVA-OH

[0070] Take a 500ml three-necked flask, first dissolve 25g of EVA in tetrahydrofuran solution, then slowly drop 40mL of sodium hydroxide / ethanol solution (0.5mol / L), and apply a reflux condenser, react at 60℃ for 5h under mechanical stirring. After the reaction is completed, add 22.5mL of HCl solution (1mol / L) to neutralize the mixed solution, stir for 10 minutes, and stop the reaction. Pour into 500ml of distilled water, stir continuously until precipitation occurs, filter, wash, cut up the precipitate, and dry the product at 60℃ for 12h to obtain EVA-OH.

[0071] b. Preparation of EVA-DOPO

[0072] Take a 500ml three-necked flask, add 20g EVA-OH, 3g DOPO and 200ml dichloromethane, stir and heat to 40℃, after the reactants are completely dissolved, add 7.94g carbon tetrachloride, and stir for 12h under nitrogen. After the reaction is completed, pour into 500ml distilled water, stir continuously until precipitation occurs, filter, wash, cut up the precipitate, and dry the product at 60℃ for 12h to obtain EVA-DOPO.

[0073] c. Preparation of ACA-Cl

[0074] 4.44 g (0.02 mol) of anthracenecarboxylic acid (ACA) was added into a 250 mL three-necked flask, and 100 mL of chloroform was added to dissolve it. 4 mL of thionyl chloride was slowly added dropwise under nitrogen protection, and the mixture was reacted at 50 °C for 5 h. After the reaction was completed, the solvent and unreacted thionyl chloride were removed by distillation under reduced pressure to obtain anthracenecarboxylic acid chloride (ACA-Cl).

[0075] d. Preparation of EVA-ACA

[0076] Take a 500ml three-necked flask, add 20g EVA-OH and 200ml chloroform, stir and heat to 60℃, after the reactant is completely dissolved, slowly add 5g ACA-Cl, and stir for 12h under nitrogen. After the reaction is completed, pour into 500ml distilled water, stir continuously until precipitation occurs, filter, wash, cut up the precipitate, and dry the product at 60℃ for 12h to obtain EVA-ACA.

[0077] e. Preparation of EVA-DC

[0078] Take a 500ml three-necked flask, add 20g EVA-OH and 200ml tetrahydrofuran, stir and heat to 60℃, after the reactant is completely dissolved, slowly add 6g DC, and stir for 12h under nitrogen. After the reaction is completed, pour into 500ml distilled water, stir continuously until precipitation occurs, filter, wash, cut up the precipitate, and dry the product at 60℃ for 12h to obtain EVA-DC.

[0079] Embodiment 2:

[0080] An insulating material for a nuclear power plant cable comprises the following components in parts by weight:

[0081] Polyolefin: 35 parts of polyethylene, 5 parts of maleic anhydride grafted polyethylene;

[0082] Flame retardant unit side group grafted polyethylene EVA-ACA 58.4 parts;

[0083] 1.5 parts of multifunctional crosslinking agent trimethylol triacrylate;

[0084] Antioxidant: 0.75 parts of pentaerythritol tetrakis[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, 0.45 parts of tris[2,4-di-tert-butylphenyl]phosphite, 0.3 parts of dilauryl thiodipropionate, and 0.1 parts of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

[0085] The preparation method of the inner insulating material for the above-mentioned nuclear power plant cable is as follows: polyolefin and flame-retardant unit side-grafted polyethylene EVA-ACA are weighed according to the above-mentioned formula and mixed in an internal mixer at 150°C for 10 minutes, and then a multi-functional cross-linking agent and an antioxidant are added and mixed evenly, and then extruded and granulated at 140°C to form insulating pellets.

[0086] The obtained inner insulation pellets are used for extrusion coating on the cable 1.5mm 2 The conductive wire core is used as an inner insulating material and is irradiated and cross-linked under an electron beam with a power and energy of 10KW and 10MeV respectively, and the irradiation dose is 120KGy.

[0087] Comparative Example 2:

[0088] The insulating material of this comparative example is the same as that of Example 2, except that 58.4 parts of the flame-retardant unit side-grafted polyethylene EVA-ACA in Example 2 are replaced with polyethylene, and the other formula compositions and preparation methods are exactly the same.

[0089] Embodiment 3:

[0090] An insulating material for a nuclear power plant cable comprises the following components in parts by weight:

[0091] Polyolefin: 5 parts of ethylene-vinyl acetate copolymer, 5 parts of maleic anhydride grafted hydrogenated styrene-butadiene-styrene block copolymer;

[0092] Flame retardant unit side group grafted polyethylene EVA-DOPO 85.9 parts;

[0093] Multifunctional cross-linking agent: 3 parts of triallyl isocyanurate;

[0094] Antioxidant: 0.5 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 0.5 parts of pentaerythritol tetrakis(3-laurylthiopropionate), and 0.1 parts of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl]hydrazine.

[0095] The preparation method of the inner insulating material for the above-mentioned nuclear power plant cable is as follows: polyolefin and flame-retardant unit side-grafted polyethylene EVA-DOPO are weighed according to the above-mentioned formula and mixed in an internal mixer at 170°C for 10 minutes, and then a multi-functional cross-linking agent and an antioxidant are added and mixed evenly, and then extruded and granulated at 170°C to form insulating pellets.

[0096] The obtained inner insulation granules are used for extrusion coating on the cable 2.5mm 2 The conductive wire core is used as an insulating material and is irradiated and cross-linked under an electron beam with a power and energy of 10KW and 10MeV respectively, and the irradiation dose is 160KGy.

[0097] Comparative Example 3:

[0098] The insulating material of this comparative example is the same as that of Example 3, except that 85.9 parts of the flame-retardant unit side-grafted polyethylene EVA-DOPO in Example 3 are replaced with ethylene-vinyl acetate copolymer, and the other formula compositions and preparation methods are exactly the same.

[0099] Embodiment 4:

[0100] An insulating material for a nuclear power plant cable comprises the following components in parts by weight:

[0101] Polyolefin: 5 parts of maleic anhydride grafted polyethylene-octene copolymer;

[0102] Flame retardant unit side group grafted polyethylene EVA-DC 92.4 parts;

[0103] 1.5 parts of multifunctional crosslinking agent trimethylol triacrylate;

[0104] Antioxidant: 0.5 parts of pentaerythritol tetrakis[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, 0.25 parts of tris[2,4-di-tert-butylphenyl]phosphite, 0.25 parts of dilauryl thiodipropionate, and 0.1 parts of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

[0105] The preparation method of the inner insulating material for the above-mentioned nuclear power plant cable is as follows: polyolefin and flame-retardant unit side-grafted polyethylene EVA-DC are weighed according to the above-mentioned formula and mixed in an internal mixer at 140°C for 10 minutes, and then a multi-functional cross-linking agent and an antioxidant are added and mixed evenly, and then extruded and granulated at 140°C to form insulating pellets.

[0106] The obtained inner insulation pellets are used for extrusion coating on the cable 1.5mm 2 The conductive wire core is used as an inner insulating material and is irradiated and cross-linked under an electron beam with a power and energy of 10KW and 10MeV respectively, and the irradiation dose is 180KGy.

[0107] Comparative Example 4:

[0108] The insulating material of this comparative example is the same as that of Example 4, except that: 92.4 parts of the flame retardant unit side-grafted polyethylene EVA-DC in Example 4 are all replaced with polyethylene-octene copolymer, and the other formula composition and preparation method are exactly the same.

[0109] Embodiment 5:

[0110] A halogen-free flame-retardant polyolefin sheath material for a nuclear power plant comprises the following components in parts by weight:

[0111] Polyolefin: 16 parts of ethylene-octene copolymer, 5 parts of maleic anhydride grafted polyethylene-octene copolymer;

[0112] Flame retardant unit side-grafted polyethylene: EVA-ACA 25 parts;

[0113] Microencapsulated halogen-free flame retardant: 40 parts of polyphosphazene microencapsulated zinc aluminum double hydroxide, 7 parts of polyphosphazene microencapsulated inorganic aluminum hypophosphite, 23 parts of polyphosphazene microencapsulated zinc aluminate;

[0114] Multifunctional flame retardant synergist: 1 part of graphene hybrid loaded with bismuth carbonate nanoparticles anti-radiation agent;

[0115] Multifunctional crosslinking agent: 2 parts of pentaerythritol triacrylate;

[0116] Lubricant: 0.8 parts of silicone powder, 0.2 parts of PE wax;

[0117] Antioxidant: 0.5 parts of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, 0.3 parts of bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, 0.1 parts of 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and 0.1 parts of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

[0118] The preparation method of the microencapsulated flame retardant is as follows:

[0119] Preparation of polyphosphazene microencapsulated zinc aluminum double hydroxide: under ice water bath conditions, add 200 parts by mass of pyridine, 10 parts by mass of melamine, 20 parts by mass of 4,4'-diaminodiphenyl ether and 100 parts by mass of core flame retardant: zinc aluminum double hydroxide to a reactor equipped with a stirrer, a reflux condenser and dry nitrogen, and stir evenly to obtain a mixed solution A; dissolve 20 parts by mass of hexachlorocyclotriphosphazene in 50 parts by mass of pyridine to form a mixed solution B; add the mixed solution B dropwise to the mixed solution A at a rate of 3 mL / min, and after the dropwise addition is completed, heat the mixture from the ice water bath temperature to 80° C. and react for 12 hours. After the reaction is completed, filter, wash with water, and dry the obtained product in sequence to obtain a microencapsulated flame retardant with a shell layer of polyphosphazene and a core of zinc aluminum double hydroxide;

[0120] The preparation method of polyphosphazene microencapsulated inorganic aluminum hypophosphite or polyphosphazene microencapsulated zinc aluminate is the same as the preparation method of polyphosphazene microencapsulated zinc aluminum double hydroxide, except that the core is replaced by inorganic aluminum hypophosphite or zinc aluminate.

[0121] The preparation method of the multifunctional flame retardant synergist is as follows:

[0122] Under room temperature conditions, 250 parts by mass of distilled water and 3 parts by mass of graphene are added to a reaction container equipped with a stirrer, a reflux condenser and dry nitrogen, and ultrasonic treatment is performed for 30 minutes under room temperature conditions, and then 3 parts by mass of bismuth chloride, a precursor of a nanoparticle anti-radiation agent, is added, 1 mol / L sodium carbonate solution is added dropwise to adjust the pH to 10 and stirred, and after the dropwise addition is completed, the mixture is transferred to a hydrothermal reactor and subjected to a hydrothermal reaction at 180° C. for 12 hours. After the reaction is completed, the product is centrifuged, washed with water, washed with ethanol, and dried in a vacuum oven at 80° C. to obtain graphene loaded with bismuth carbonate nanoparticle anti-radiation agent.

[0123] Preparation method of the above-mentioned halogen-free flame-retardant sheath material for nuclear power plants:

[0124] According to the formula, polyolefin and flame retardant unit side-grafted polyethylene are weighed and mixed in an internal mixer at 140°C until uniform, and then microencapsulated halogen-free flame retardant, multifunctional flame retardant synergist, multifunctional cross-linking agent, antioxidant and lubricant are added. After mixing evenly, the mixture is extruded and granulated at 140°C to prepare sheath granules.

[0125] The prepared sheath granules are used for the outer sheath layer of the cable conductive core. When the sheath granules are used as the coating material of the cable conductive core insulation layer, they need to be irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 240KGy.

[0126] Comparative Example 5:

[0127] The sheath material of this comparative example is the same as that of Example 5, except that 25 parts of the flame retardant unit side-grafted polyethylene EVA-ACA in Example 5 are replaced with polyethylene-octene copolymer, and the other formula compositions and preparation methods are exactly the same.

[0128] Embodiment 6:

[0129] A halogen-free flame-retardant sheath material for a nuclear power plant, comprising the following components in parts by weight:

[0130] Polyolefin: 10 parts of ethylene-vinyl acetate copolymer, 5 parts of maleic anhydride grafted EPDM rubber;

[0131] Flame retardant unit side group grafted polyethylene EVA-DOPO 40 parts;

[0132] Microencapsulated halogen-free flame retardant: The following microencapsulated flame retardant was prepared according to the method of Example 1 disclosed in Chinese Patent 201410016870.8, comprising 25 parts of hyperbranched carbon-forming agent shell microencapsulated core magnesium hydroxide, 8 parts of hyperbranched carbon-forming agent shell microencapsulated core ammonium polyphosphate, and 2 parts of hyperbranched carbon-forming agent shell microencapsulated zinc stannate;

[0133] Multifunctional flame retardant synergist: 5 parts of graphene hybrid loaded with lanthanum oxide nanoparticles anti-radiation agent;

[0134] Multifunctional crosslinking agent: 3 parts of trimethylolpropane trimethacrylate;

[0135] Lubricant: 0.4 parts of silicone powder, 0.1 parts of zinc stearate;

[0136] Antioxidant: 0.8 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 0.3 parts of distearyl thiodipropionate, 0.3 parts of pentaerythritol tetrakis(3-laurylthiopropionate), and 0.1 parts of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl]hydrazine.

[0137] The preparation method of the multifunctional flame retardant synergist is as follows:

[0138] Under room temperature conditions, 200 parts by mass of distilled water and 3 parts by mass of graphene are added to a reaction container equipped with a stirrer, a reflux condenser and dry nitrogen. The mixture is ultrasonicated for 30 minutes at room temperature, and then 4 parts by mass of lanthanum chloride, a precursor of a nanoparticle anti-radiation agent, are added. A 25wt% ammonia solution is added dropwise to adjust the pH to 10 and stirred. After the addition is completed, the mixture is heated to 80°C and reacted for 24 hours. After the reaction is completed, the product is centrifuged, washed with water, washed with ethanol, and dried in a vacuum oven at 80°C to obtain graphene loaded with lanthanum oxide nanoparticle anti-radiation agent.

[0139] Preparation method of the above-mentioned halogen-free flame-retardant sheath material for nuclear power plants:

[0140] According to the formula, polyolefin and flame retardant unit side-grafted polyethylene are weighed and mixed in an internal mixer at 180°C until uniform, and then microencapsulated halogen-free flame retardant, multifunctional flame retardant synergist, multifunctional cross-linking agent, antioxidant and lubricant are added. After mixing evenly, the mixture is extruded and granulated at 180°C to prepare sheath granules.

[0141] The prepared sheath granules are used for the outer sheath layer of the cable conductive core. When the inner insulating granules are used as the coating material of the inner insulating layer of the cable conductive core, they need to be irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 100KGy.

[0142] Comparative Example 6:

[0143] The sheath material of this comparative example is the same as that of Example 6, except that: 40 parts of the flame retardant unit side-grafted polyethylene EVA-DOPO in Example 6 are replaced with polyethylene-vinyl acetate copolymer, and the other formula composition and preparation method are exactly the same.

[0144] Embodiment 7:

[0145] A halogen-free flame-retardant sheath material for a nuclear power plant, comprising the following components in parts by weight:

[0146] Polyolefin: 10 parts of EPDM rubber, 5 parts of maleic anhydride grafted EPDM rubber;

[0147] Flame retardant unit side group grafted polyethylene EVA-DC 40 parts;

[0148] Microencapsulated halogen-free flame retardant: The following microencapsulated flame retardant was prepared according to the method of Example 1 disclosed in Chinese Patent No. 200810156885.9, 25 parts of nickel iron double hydroxide in a silica gel shell microencapsulated core, and 15 parts of melamine polyphosphate in a silica gel shell microencapsulated core;

[0149] Multifunctional flame retardant synergist: 2 parts of graphene hybrid loaded with silica nanoparticles anti-radiation agent;

[0150] Multifunctional crosslinking agent: 2.5 parts of trimethylol triacrylate;

[0151] Lubricant: 0.5 parts of silicone powder, 0.2 parts of PE wax;

[0152] Antioxidant: 1 part of pentaerythritol tetrakis[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, 0.4 part of bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite, 0.3 part of 6,6'-di-tert-butyl-2,2'-thiodi-p-cresol, 0.1 part of N,N'-bis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

[0153] The preparation method of the multifunctional flame retardant synergist is as follows:

[0154] Under room temperature conditions, 180 parts by mass of distilled water and 3 parts by mass of graphene are added to a reaction container equipped with a stirrer, a reflux condenser and dry nitrogen. The mixture is ultrasonicated at room temperature for 30 minutes, and then 5 parts by mass of tetraethyl orthosilicate, a precursor of a nanoparticle anti-radiation agent, are added. A 25wt% ammonia solution is added dropwise to adjust the pH to 10 and stirred. After the addition is completed, the temperature is raised to 80°C and the reaction is carried out for 24 hours. After the reaction is completed, the product is centrifuged, washed with water, washed with ethanol, and dried in a vacuum oven at 80°C to obtain graphene loaded with a silica nanoparticle anti-radiation agent.

[0155] Preparation method of the above-mentioned halogen-free flame-retardant sheath material for nuclear power plants:

[0156] According to the formula, polyolefin and flame retardant unit side-grafted polyethylene are weighed and mixed in an internal mixer at 160°C until uniform, and then microencapsulated halogen-free flame retardant, multifunctional flame retardant synergist, multifunctional cross-linking agent, antioxidant and lubricant are added. After mixing evenly, the mixture is extruded and granulated at 160°C to prepare sheath granules.

[0157] The prepared sheath granules are used for the outer sheath layer of the cable conductive core. When the inner insulating granules are used as the coating material of the inner insulating layer of the cable conductive core, they need to be irradiated and cross-linked under the power and energy of 10KW and 10MeV electron beam respectively, and the irradiation dose is 160KGy.

[0158] Comparative Example 7:

[0159] The sheath material of this comparative example is the same as that of Example 7, except that 40 parts of the flame retardant unit side-grafted polyethylene EVA-DC in Example 7 are replaced with ethylene propylene diene monomer rubber, and the other formula compositions and preparation methods are exactly the same.

[0160] The insulating material of Example 2-3-4 and the insulating material of Comparative Example 2-3-4 were made into sheets according to the radiation cross-linking treatment in the corresponding embodiments, and the mechanical properties, thermal aging life and radiation resistance of the insulating materials were tested. The test results are shown in Table 1 below.

[0161] Table 1 Nuclear power polyolefin insulation material properties of Example 2-3-4 and Comparative Example 2-3-4

[0162]

[0163]

[0164] The results show that Examples 2, 3 and 4 using flame retardant unit side-group grafted polyethylene have better flame retardant properties, radiation resistance and longer heat aging life than the comparative experimental formulation using commercial polyolefins.

[0165] The sheath material of Example 5-6-7 and the sheath material of Comparative Example 5-6-7 were made into sheets by radiation cross-linking treatment according to the corresponding embodiments, and the performance of the sheath material was tested. The test results are shown in Table 2 below.

[0166] Table 2 Nuclear power polyolefin sheath material properties of Example 5-6-7 and Comparative Example 5-6-7

[0167]

[0168]

[0169] The results show that Examples 5, 6 and 7 using flame retardant unit side-group grafted polyethylene have better flame retardancy, media resistance, radiation resistance and longer heat aging life than the comparative experimental formula using commercial polyolefins.

Claims

1. A halogen-free flame-retardant polyolefin material obtained by mixing and kneading the following raw materials in parts by weight: 5-45 parts of polyolefin, 40-95 parts of flame retardant unit side-group grafted polyethylene, 0.5-5 parts of multifunctional crosslinking agent, and 0.5-4 parts of antioxidant; The multifunctional cross-linking agent is selected from one or more of triallyl cyanurate, triallyl isocyanurate, trimethylol propane trimethacrylate, trimethylol triacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate in any proportion; The flame retardant unit side-group grafted polyethylene is composed of ethylene-vinyl acetate copolymer EVA hydrolyzed grafted flame retardant structural units, wherein the flame retardant structural units are flame retardants containing phosphorus or benzene ring structure; the grafting amount of the flame retardant structural units is 15-35%.

2. The halogen-free flame-retardant polyolefin material according to claim 1, characterized in that: The flame retardant structural unit is selected from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, diphenylphosphinyl chloride or anthracenecarboxylic acid.

3. The halogen-free flame-retardant polyolefin material according to claim 2, characterized in that The flame retardant unit side group grafted polyethylene is prepared by a method comprising the following steps: Step 1: Add EVA to the solvent and stir, and heat to 40°C. After EVA is completely dissolved, add sodium hydroxide ethanol solution and stir at this temperature for 2-5 hours for hydrolysis, and then add hydrochloric acid solution for neutralization reaction; after the reaction is completed, pour the reaction solution into distilled water and stir continuously until all precipitates are precipitated, filter, wash and dry to obtain EVA-OH product; Step 2: Add EVA-OH to the solvent and stir, and heat to 40°C. After EVA-OH is completely dissolved, add diphenylphosphine chloride to the system, stir for 12 hours through nitrogen, wash and dry with anhydrous methanol to obtain flame-retardant unit side group DC grafted polyethylene.

4. The halogen-free flame-retardant polyolefin material according to claim 2, characterized in that The flame retardant unit side group grafted polyethylene is prepared by a method comprising the following steps: Step 1: Add EVA to the solvent and stir, and heat to 40°C. After EVA is completely dissolved, add sodium hydroxide ethanol solution and stir at this temperature for 2-5 hours for hydrolysis, and then add hydrochloric acid solution for neutralization reaction; after the reaction is completed, pour the reaction solution into distilled water and stir continuously until all precipitates are precipitated, filter, wash and dry to obtain EVA-OH product; Step 2: With anthracenecarboxylic acid as a raw material, thionyl chloride and a solvent are added to the reaction system, and the temperature is raised to 40-60°C in a nitrogen atmosphere for reaction; after the reaction is completed, the temperature is lowered to room temperature, and the solvent is recovered by rotary evaporation to obtain a viscous liquid product, namely anthracenecarboxylic acid chloride ACA-Cl; EVA-OH is added to the solvent and stirred, and the temperature is raised to 40°C. After EVA-OH is completely dissolved, anthracenecarboxylic acid chloride ACA-Cl is added dropwise to the above solution, and nitrogen is passed through and stirred for 12 hours, and the solution is washed and dried with anhydrous methanol to obtain a flame-retardant unit side group ACA grafted polyethylene.

5. The halogen-free flame-retardant polyolefin material according to claim 2, characterized in that The flame retardant unit side group grafted polyethylene is prepared by a method comprising the following steps: Step 1: Add EVA to the solvent and stir, and heat to 40°C. After EVA is completely dissolved, add sodium hydroxide ethanol solution and stir at this temperature for 2-5 hours for hydrolysis, and then add hydrochloric acid solution for neutralization reaction; after the reaction is completed, pour the reaction solution into distilled water and stir continuously until all precipitates are precipitated, filter, wash and dry to obtain EVA-OH product; Step 2: Add EVA-OH and DOPO to the solvent, stir, and heat to 40°C. After EVA-OH and DOPO are completely dissolved, add carbon tetrachloride dropwise to the above solution, stir for 12 hours under nitrogen, wash with anhydrous methanol, and dry to obtain flame-retardant unit side group DOPO grafted polyethylene.

6. Use of the halogen-free flame-retardant polyolefin material according to any one of claims 1 to 5 in preparing the insulating layer of the conductive core of cables for nuclear power plants.

7. The use according to claim 6, characterized in that The steps include: Polyolefin and flame-retardant unit side-grafted polyethylene are weighed according to the proportion, mixed in an internal mixer at 140°C-200°C for 5-20 minutes, and then a multifunctional cross-linking agent and an antioxidant are added. After mixing evenly, the mixture is extruded and granulated at 140°C-200°C to obtain pellets; the pellets are used as the coating material of the insulation layer of the cable conductive core, and are subjected to radiation cross-linking treatment.

8. A halogen-free flame-retardant polyolefin material obtained by mixing and kneading the following raw materials in parts by weight: 5-30 parts of polyolefin, 25-40 parts of flame retardant unit side-group grafted polyethylene, 40-50 parts of microencapsulated halogen-free flame retardant, 1-5 parts of multifunctional flame retardant synergist, 1-3 parts of multifunctional cross-linking agent, 0.5-2 parts of lubricant, 1-4 parts of antioxidant; The multifunctional cross-linking agent is selected from one or more of triallyl cyanurate, triallyl isocyanurate, trimethylol propane trimethacrylate, trimethylol triacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate in any proportion; The flame retardant unit side-group grafted polyethylene is composed of ethylene-vinyl acetate copolymer EVA hydrolyzed grafted flame retardant structural units, wherein the flame retardant structural unit is a flame retardant containing phosphorus or a benzene ring structure; the grafting amount of the flame retardant structural unit is 15-35%; The microencapsulated halogen-free flame retardant is composed of a shell material and a core flame retardant; the shell material is selected from one of silicone gel, hyperbranched carbon-forming agent, and polyphosphazene; the core flame retardant is selected from one of aluminum hydroxide, magnesium hydroxide, magnesium aluminum double hydroxide, zinc aluminum double hydroxide, magnesium iron double hydroxide, zinc iron double hydroxide, nickel iron double hydroxide, ammonium polyphosphate, pentaerythritol, melamine, melamine phosphate, melamine cyanurate, inorganic aluminum hypophosphite, organic aluminum hypophosphite, triazine carbon-forming agent, piperazine pyrophosphate, zinc borate, zinc aluminate, zinc stannate, and low-melting point glass powder, and one or more thereof are mixed in any proportion; The multifunctional flame retardant synergist consists of a nanoparticle anti-radiation agent and graphene; the nanoparticle anti-radiation agent is selected from one or more of tungsten oxide, bismuth oxide, bismuth carbonate, rare earth metal oxides, and nano silicon dioxide and mixed in any proportion; the rare earth metal in the rare earth metal oxide is one of lanthanum, cerium, praseodymium, neodymium, promethium, samarium, and europium.

9. The halogen-free flame-retardant polyolefin material according to claim 8, characterized in that: The flame retardant structural unit is selected from 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, diphenylphosphinyl chloride or anthracenecarboxylic acid.

10. The halogen-free flame-retardant polyolefin material according to claim 8, characterized in that The preparation method of the multifunctional flame retardant synergist comprises the following steps: The graphene is mixed with water and ultrasonically treated for 20-40 minutes, and then the corresponding precursor of the nanoparticle anti-radiation agent is added. Under nitrogen protection and stirring, an alkaline regulator is added dropwise to make the pH of the system 9-11. After the addition is completed, the temperature is raised to react. After the reaction is completed, centrifugal separation, water washing, alcohol washing and drying are performed to obtain graphene loaded with the nanoparticle anti-radiation agent, which is a multifunctional flame retardant synergist; The corresponding precursor of the nanoparticle anti-radiation agent is tungsten chloride, bismuth chloride, chloride-based rare earth metal salt or tetraethyl orthosilicate.

11. Use of the halogen-free flame-retardant polyolefin material according to any one of claims 8 to 10 in preparing an outer sheath layer of a conductive core of a cable for a nuclear power plant.

12. The use according to claim 11, characterized in that The steps include: Polyolefin and flame retardant unit side-grafted polyethylene are weighed according to the proportion, mixed in an internal mixer at 140°C-200°C until uniform, and then microencapsulated halogen-free flame retardant, multifunctional flame retardant synergist, multifunctional cross-linking agent, antioxidant and lubricant are added. After mixing evenly, the mixture is extruded and granulated at 140°C-200°C to obtain pellets; the obtained pellets are used as the outer sheath material of the cable conductive core, and are subjected to radiation cross-linking treatment.

Citation Information

Patent Citations

  • Temperature-resistant oil-resistant low-smoke halogen-free flame-retardant radiation cross-linked polyolefin composite material and preparation method thereof

    CN103756121A

  • Low-smoke halogen-free flame-retardant polyolefin cable material and preparation method thereof

    CN116355306A

  • Halogen-free flame-retardant antioxidant cross-linked polyolefin composite material and preparation method thereof

    CN117384445A